MEKANISME PEMBERHENTIAN KEPALA DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2004 TENTANG PEMERINTAHAN DAERAH ( STUDI KASUS PEMBERHENTIAN BUPATI GARUT PADA TAHUN 2013 ) - AL QAYUM, M. SADMI; Haryono, Dodi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
This research’s aim was to determined the procedures and dismissal of the regional head based on Undang-Undang Nomor 32 Tahun 2004 Tentang Pemerintahan Daerah , as well as determine whether the decision of the Mahkamah Agung Nomor 1P/KHS/2013 Tentang Pemberhentian Bupati Garut Tahun 2013 was accordance with the legislation of Indonesia.This research used a normative approach and secondary file as legal materials . The file’s collection was a document form or library’s research that include studies of primary legal materials, secondary legal materials, and tertiary legal materials . The analysis is qualitative analysis and drawing by deductive conclusions.The results showed that the substance of the dismissal of the regional head was regulated in Undang-Undang Nomor 32 Tahun 2004 Tentang Pemerintahan Daerah even in Pasal 29 Undang-Undang Nomor 32 Tahun 2004 Pemerintahan Daerah still has a multiple interpretations such as : No able to carry out tasks or ongoing basis or permanently unavailable consecutively for six months, no longer qualifies as a regional head , an apparent violation of the oath of regional head. The decision of Mahkamah Agung Nomor 1P/Khs/2013 can be seen in the weight of consideren’s dictum and such decision , which basically accepts the plea of Garut’s Folk Representative Council about the dismissal of Garut’s regional head. Keywords : Termination , Regional Head , Legal Due